Can We Avoid Maladaptation At All? - Asare-Nuamah, Peter (My University, 2023)
The impact of climate change especially in developing economies has called for heightened global attention to tackle climate change. Yet, amidst the urgency to address climate change, emerging literature shows that existing climate change adaptation strategies have the potential to be counterproductive, further worsening the vulnerability of already fragile and vulnerable communities. Indeed, maladaptation cannot to completely avoided, but it can be substantially minimized. Achieving this requires a strong collaboration between science, policy, and practice interface.
Keywords: maladaptation; climate change; developing economies